IMPLEMENTATION OF AN ELECTRO-PNEUMATIC SYSTEM IN A VALVE SAFETY SUPPORT DEVICE THROUGH LINEAR TO ROTATIONAL MOTION - BILHAN GAMALIEL (CV KULTURA DIGITAL MEDIA, 2024)
This research aims to develop a tool that can be used in the process of clamping valves on motorbike engine blocks using a pneumatic system as a mechanism for clamping the engine block and as a rack and pinion driver, replacing human hand movements semi-automatically through electropneumatic control. This aims to save time in the clamping process, which usually takes around 90 to 120 minutes manually. By using this valve adjustment tool, clamping time can be cut to 10 to 17.5 minutes. Research methods include design, component manufacturing, assembly, testing, and data collection. The results of the development of a valve control tool with an electro-pneumatic system can also be applied in the learning process of mechanical engineering students in the fluid control laboratory.